HUBUNGAN ANTARA KEKERASAN VERBAL DENGAN PERILAKU AGRESIF ANAK USIA 4-6 TAHUN - Salfina Rahma Agustina; Nurhenti Dorlina Simatupang (Pelangi Jurnal Pemikiran dan Penelitian Islam Anak Usia Dini, 2022)
This research is based on the background of aggressive behavior that appears in children who experience verbal violence in the Dharma Wanita Persatuan Waru Kindergarten. The purpose of this study was to determine whether there was a relationship between verbal violence and aggressive behavior in children aged 4-6 years. This research uses correlational quantitative research with 30 samples. Data analysis of this research uses product-moment correlation data analysis with a prerequisite test for normality test and linearity test. The results showed that there was a relationship between verbal violence and aggressive behavior in children aged 4-6 years or Ha was accepted and Ho was rejected because the value of the r-Pearson correlation was 0.869 in the range of r-person correlation values ??(0.81 – 0.99), which means that between variable x (verbal violence) with variable y (aggressive behavior) has a relationship with the high category. In addition, the results of the educational background of parents at Dharma Wanita Persatuan Waru Kindergarten are low, namely at the elementary school (20%), junior high school (26%), junior high/vocational school (46%), D1-D3 (3%), S1 ( 3%). So it can be concluded that the education factor of parents is the cause of verbal abuse to children so that children show aggressive behavior that can disturb themselves and others.